Validasi Kelayakan E-Modul Pajak Penghasilan Berbasis Canva dalam Pembelajaran Perpajakan di Sekolah Menengah Kejuruan - Anggraini, Yovita Dwi; Jaenudin, Riswan; Safitri , Erna Retna (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the feasibility of a Canva-based Income Tax e-module as a learning medium in Vocational High Schools (SMK). It is part of a development research project using a descriptive quantitative approach, with expert validation as the main method. Three validators were involved in the validation process, consisting of a subject matter expert, a language expert, and a media expert. The instrument used was an assessment sheet employing a Likert scale to evaluate the feasibility of the e-module in terms of content accuracy, language use, and media design. The validation results showed that the e-module received an average score of 88% from the content expert, 94% from the language expert, and 89% from the media expert, all of which fall under the "Highly Feasible" category. These results indicate that the e-module meets quality standards in terms of accurate and relevant content, clear and communicative language, and visually engaging media design that supports the learning process. Based on these findings, it can be concluded that the Canva-based Income Tax e-module is highly suitable for use as a learning tool in vocational education. The e-module is considered effective for supporting self-directed, interactive, and engaging learning, aligned with the needs of students in the digital era. Therefore, it is expected that this e-module can enhance the effectiveness, engagement, and overall quality of income tax instruction in vocational high schools, contributing positively to the teaching and learning process in accounting and taxation subjects.